Profile design of twin screw air compressor for fuel cell - Maofei Geng; Le Wang; Dong Cui; Xiaosa Li; Jinlu Li; Huijun Jiang (Energy Reports, 2022)
Hydrogen–oxygen vehicle fuel cells have high research and development prospect because of their advantages of environmental protection, pollution-free and high energy conversion efficiency. Air compressor is an important part of vehicle fuel cell system. Dry twin screw compressors have been applied very well in bus fuel cell system. Aiming at the characteristics of low pressure ratio and large flow rate of fuel cell air compressors, a kind of 3–5 twin screw air compressor profile was designed, and the design method was given.